Ferrule abrasives
Patent Information
- Application Number
- JP2023514608
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-15
- Filing Date
- 2022-03-31
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-03-31
AI Technical Summary
【0012】 本発明のフェルール用研磨材は上記構成を有することからフェルールの研磨性能が高い上に耐久性も向上できる。
Smart Images

Figure 0007634654000001 
Figure 0007634654000002 
Figure 0007634654000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an abrasive for ferrules used for polishing the end surface of a ferrule. [Background technology]
[0002] Optical fibers used as a transmission means for optical communications are required to have as little optical loss as possible due to the recent demand for larger capacity and higher efficiency. Optical connectors are used to connect optical fibers to each other. Optical connectors have a ferrule. An insertion hole through which the optical fiber is inserted is formed in the ferrule. The optical fiber is fixed to the ferrule with an adhesive or the like.
[0003] The quality of the connection end face of an optical connector is very important because it affects the optical characteristics of the optical fiber. Therefore, the end face of an optical connector is polished to a mirror finish through multiple stages. As a final polishing step, a precise mirror finish is performed using a polishing material such as a polishing sheet with a polishing layer containing fine abrasive grains, a polishing tape, a polishing stone, or a polishing cloth (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-1803 A Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, in order to realize high capacity optical fibers, multi-core optical fibers that bundle a number of optical fibers have been developed. Multi-core ferrules are used to connect multi-core optical fibers, and their end faces require a more precise mirror finish. Even for single-core optical fibers, a plurality of ferrules may be polished simultaneously to improve workability, and a precise mirror finish is required in the same way as for multi-core ferrules. To achieve a precise mirror finish, it is desirable for the abrasive to be highly durable and to deteriorate little with use. Furthermore, if the abrasive does not deteriorate much, it can be used continuously, improving workability.
[0006] The present invention has been completed in view of the above-mentioned circumstances, and an object of the present invention is to provide a high-performance abrasive for ferrules that is suitable for polishing ferrules. [Means for solving the problem]
[0007] When polishing a multi-core ferrule or a plurality of ferrules, it is desired that the heights of the optical fibers are higher than a predetermined value and uniform after polishing, and it is required to realize a uniform polished state with a small amount of polishing. It is also required that the polished surface is not scratched and that the generation of a core dip that constitutes the optical fiber is suppressed.
[0008] Some of these requirements are contradictory. The inventors conducted extensive research to solve the above problems, and found that the height of the optical fiber was improved by including small grain size abrasives, and that the suppression of core dip was achieved by using silica as the abrasives. They also found that the surface could be polished without scratches by increasing the amount of abrasives and including abrasives of a certain size. They also found that durability could be improved by using epoxy resin as the binder that holds the abrasives.
[0009] That is, the abrasive for ferrules of the present invention, which solves the above problems, comprises a binder made of a resin material and abrasive grains dispersed in the binder. The resin material is entirely cross-linked. The abrasive grains are contained in an amount of 80% to 91% based on the sum of the masses of the abrasive grains and the binder, and 62.5% to 80% based on the mass of the abrasive grains are small particles having a particle diameter of 100 nm or less, and are composed of silica.
[0010] In particular, the resin material preferably contains 93% or more of epoxy resin based on its mass. The epoxy resin is preferably a biphenyl type. The binder preferably has a pencil hardness of 3H or more. The small diameter particles are preferably particles having a peak top particle size of 50 nm or less. By controlling the particle size within this range, it becomes easier to achieve uniformity in the height of the optical fiber.
[0011] Furthermore, it is preferable that the abrasive grains contain grains having a peak top grain size of 150 nm or more, since this makes it easier to ensure that the surface after polishing is free of scratches. Effect of the Invention
[0012] Since the abrasive for ferrules of the present invention has the above-mentioned configuration, it has high abrasive performance for ferrules and also has improved durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The ferrule abrasive of the present invention will be described in detail below based on the embodiment. The ferrule abrasive of this embodiment is a member for polishing the end face of a ferrule. A ferrule is a member for performing termination processing of an optical fiber and is a member that constitutes an optical connector that connects optical fibers together.
[0014] The ferrule abrasive of this embodiment is composed of abrasive grains, a binder for dispersing the abrasive grains, and other necessary components. It is preferable to use the abrasive grains and the binder for dispersing the abrasive grains as a layered abrasive layer. When used as an abrasive layer, the thickness is preferably 5 μm or less, and more preferably 3 μm or less. Reducing the thickness improves the durability of the abrasive layer.
[0015] The abrasive grains are contained in an amount of 80% or more and 91% or less based on the sum of the masses of the abrasive grains and the binder. In particular, the lower limit may be 85%, 86%, 87%, or 87.5%, and the upper limit may be 90%, 89%, 88%, or 87.5%. These upper and lower limits may be combined in any combination.
[0016] The abrasive grains are composed of silica. Materials other than silica can be mixed, but the amount of silica is preferably 95% or more, more preferably 97.5% or more, and even more preferably 99% or more, based on the mass of the entire abrasive grains. Materials other than silica can be contained as particles separate from the particles made of silica, or can be contained in the same particles as silica.
[0017] The particle size distribution of the abrasive grains is specified. Specifically, based on the mass of the entire abrasive grains, small diameter particles are present at 62.5% to 80%. The lower limit of the amount of small diameter particles can be 65%, 70%, 72.5%, or 75%. The upper limit can be 79%, 78%, 77%, 76%, or 75%. These upper and lower limits can be arbitrarily combined. Small diameter particles are particles having a particle size below a certain particle size. The certain particle size is preferably particles having a particle size of 0.1 μm or less, more preferably particles having a particle size of 30 nm or less, and more preferably particles having a particle size of 20 nm or less. It is preferable that the small diameter particles have a peak top at a particle size below the aforementioned certain particle size. The peak top means that a peak is present when the particle size distribution is expressed on a volume basis, and the particle size at the peak top refers to the particle size at that peak. It is preferable that the particle size at the peak top is a mode diameter within a range of particle sizes below a certain particle size. The peak top particle size of the small diameter particles is preferably 50 nm or less, more preferably 30 nm or less, and even more preferably 20 nm or less.
[0018] The shape of the abrasive grains is not particularly limited, but spherical silica, crushed silica, etc. can be used. It is preferable to contain particles with a particle size of 100 nm or more. In particular, it is preferable to have a peak top, and the particle size of the peak top is 150 nm or more, and more preferably 200 nm or more. Furthermore, it is preferable not to contain particles with a particle size of 5 μm or more in order to suppress scratches on the polished surface. It is preferable to contain crushed silica.
[0019] In this specification, the "particle size" is a value measured using a combination of a laser diffraction / scattering particle size distribution analyzer (LA-750: manufactured by Horiba, Ltd.) and a dynamic light scattering Nanotrac particle size distribution analyzer (UPA-EX150: manufactured by Nikkiso Co., Ltd.).
[0020] Specifically, a laser diffraction / scattering particle size analyzer is used in 700 mode to measure the flow cell of a fluid to which several drops of slurry have been dropped, allowing the range of larger particle sizes to be measured, while a dynamic light scattering Nanotrac particle size analyzer is used to measure the particle sizes of particles with a diameter of 100 nm or less in a batchwise manner after dispersing the particles in methyl ethyl ketone. The particle size distribution is measured by combining the results of both measurements.
[0021] Spherical silica can be produced by reacting metal silicon with oxygen. By using this method, it is easy to obtain spherical silica with an average particle size of about 0.05 μm to 10 μm.
[0022] Crushed silica is a fine particle that can be produced by crushing silica. Its external appearance is characterized by an angular surface. In particular, it is desirable to adopt a form that can be obtained by crushing the aforementioned spherical silica. There is no particular limitation on the crushing method. For example, a bead mill, a jet mill, a ball mill, and a vibrating ball mill can be used.
[0023] The abrasive grains can be surface-treated. An example of the surface treatment is a method using a silane compound. Examples of the silane compound include those having an epoxy group, a vinyl group, a phenylamino group, etc., and those having an epoxy group are preferred. The amount of the silane compound to be treated is not particularly limited, but examples of the amount of the silane compound to be treated include 1% or more, 2% or more, 3% or more, 4% or more, 5% or more, etc., based on the mass of the entire abrasive grains.
[0024] A resin material is used as the binder. The above-mentioned abrasive grains are dispersed in this binder to form the polishing layer. The resin material is entirely cross-linked. Here, "entirely cross-linked" means that the resin material contains 98% or more (preferably 99% or more, and more preferably substantially 100%) of cross-linkable precursors based on the mass of the entire resin material. An example of a cross-linkable precursor is an epoxy resin. When an epoxy resin precursor is copolymerized with another precursor, the component derived from the epoxy resin means only the portion of one molecular chain derived from the epoxy resin precursor.
[0025] The epoxy resin is not particularly limited. Bisphenol type (A type, F type, a mixture of A type and F type, etc.), biphenyl type, etc. can be used, and biphenyl type is preferable. Biphenyl type epoxy resin is a resin obtained by reacting a precursor of an epoxy resin having a biphenyl skeleton.
[0026] Biphenyl type epoxy resins exhibit high heat resistance due to the rigidity of the biphenyl structure. In addition, the biphenyl structure has high linearity, and when cured, has high plastic deformation ability. The biphenyl skeleton of the biphenyl type epoxy resin can be a halogen-substituted product, an alkyl-substituted product, a hydrogen-added product, or the like. In particular, methyl-substituted products are preferably used from the viewpoint of handling.
[0027] Commercially available precursors of bisphenol-type epoxy resins include ZX-1059 (Nippon Steel Chemical & Material Co., Ltd.). Commercially available precursors of epoxy resins having a biphenyl skeleton include "jER (registered trademark)" YX4000H, YX4000, YL6616, YL6121H, YL6640, and YL6677 (all manufactured by Japan Epoxy Resins Co., Ltd.), and NC3000 (manufactured by Nippon Kayaku Co., Ltd.).
[0028] As the epoxy resin, a cured product consisting of only a biphenyl type epoxy resin precursor can be used, or it can be used in combination with a bisphenol type epoxy resin precursor (such as bisphenol A). Examples of bisphenol type epoxy resin precursors include compounds represented by the following general formula: Each of the four R in the general formula can be independently selected from an alkyl group such as methyl, hydrogen, or a halogen such as chlorine, and it is particularly preferable that all of them are methyl groups.
[0029] [ka]
[0030] The curing agent for the epoxy resin is not particularly limited, but it is preferable to use a phenol-type curing agent. A curing catalyst can also be added. Commercially available curing agents include TD2131 (DIC Corporation) and MEH4500 (Meiwa Kasei Co., Ltd.).
[0031] It is preferable that the hardened epoxy resin binder has a pencil hardness of 3H or more. The pencil hardness can be increased by increasing the hardening time of the epoxy resin. For example, the lower limit of the hardening time can be 5 minutes, 8 minutes, 10 minutes, 11 minutes, 13 minutes, 14 minutes, 16 minutes, and 20 minutes.
[0032] Other necessary members include a support substrate. A film-shaped member is used as the support substrate, and a polishing layer made of abrasive grains and a binder is formed on the surface of the support substrate to provide a film-shaped abrasive for ferrules. In addition, a support substrate having an appropriate shape other than a film shape can also be used, and a polishing layer made of abrasive grains and a binder can be formed on the surface of the support substrate to obtain an abrasive for ferrules having a desired shape. Furthermore, even if there is no support substrate, a combination of abrasive grains and a binder alone can be used to form an abrasive for ferrules.
[0033] The material constituting the support substrate may be any material that has the necessary elasticity and strength and can hold the polishing layer. For example, films made of polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate, polycarbonate, etc. are suitable. When a thin film is used as the support substrate, the thickness is not particularly limited, and may be, for example, about 25 to 150 μm.
[0034] In addition, a buffer layer may be formed on the surface of the support substrate in advance depending on the purpose, such as improving the adhesion between the support substrate and the polishing layer, patterning the surface of the polishing layer, etc. For example, an easy-adhesion layer may be formed on the surface of the support substrate to form a buffer layer. The easy-adhesion layer may be formed by applying a buffer coating liquid made of, for example, epoxy resin, acrylic resin, polyester resin, etc., to the surface of the support substrate and drying it. In addition, the surface of the support substrate may be subjected to heat treatment, corona treatment, plasma treatment, etc. to form a buffer layer, and corona treatment is particularly preferred.
[0035] -Method of manufacturing ferrule abrasives The ferrule abrasive in this embodiment is manufactured by appropriately dispersing abrasive grains in a binder. The abrasive grains can be dispersed by kneading them together with the resin material constituting the binder, or by mixing and dispersing them in a precursor such as a monomer or prepolymer before the resin material is formed, and then reacting the precursor to form a resin material. In particular, it is preferable to disperse the abrasive grains in an organic solvent in advance to form a slurry, and then mix and disperse them in the binder. In this case, it is preferable to use an organic solvent that dissolves the resin (or its precursor) constituting the binder, or an organic solvent that can be mixed with the precursor itself.
[0036] The resin material constituting the binder is an epoxy resin, and in order to harden the epoxy resin, it is common to heat it at a certain temperature for a certain period of time. As for the hardening conditions, it is preferable to harden for as long a period of time as possible. Examples of the lower limit of the hardening time include 5 minutes, 8 minutes, 11 minutes, and 14 minutes, and it is particularly preferable to set the lower limit at 14 minutes.
[0037] The lower limit of the curing temperature is preferably 110° C., more preferably 120° C., and even more preferably 130° C. The upper limit of the curing temperature is preferably 180° C., more preferably 170° C., and even more preferably 160° C. These upper and lower limits can be combined in any desired manner.
[0038] An abrasive layer can be formed on the surface of the support substrate by applying a mixture of a precursor and abrasive grains to the surface of the support substrate and then reacting the precursor.
[0039] The method for obtaining silica particles constituting the abrasive grains is not particularly limited, but general methods such as a method of reacting metal silicon with oxygen, a method of melting silica by heat, a sol-gel method, etc. are employable. In particular, it is preferable to combine the method of reacting metal silicon with oxygen and the sol-gel method. EXAMPLES
[0040] (Sample preparation) Test example 1 The abrasive grains were made by mixing small-diameter silica particles with a peak top (mode diameter) of 20 nm and silica particles with a volume average diameter of 200 nm that contained almost no coarse grains of 3 μm or more, so that the content of small-diameter particles was 70% based on the mass of the abrasive grains. The binder was made by mixing a biphenyl-type epoxy resin (all R in the above chemical formula are methyl groups) as a precursor of the resin material, a trisphenolmethane derivative (MEH7500, manufactured by Meiwa Kasei Co., Ltd.) as a hardener, and triphenylphosphine as a hardening catalyst in a mass ratio of 100:95:2.
[0041] The abrasive grains and the binder were mixed in a mass ratio of 93.5:6.5 to prepare a slurry. The obtained slurry was applied to a thickness of 75 μm on the surface of a PET resin plate as a supporting substrate to a thickness of 3 μm, and then cured at 140° C. for 5 minutes to form an abrasive layer, which was used as the abrasive of Test Example 1. The surface of the supporting substrate was previously subjected to a corona treatment.
[0042] Test Examples 2 and 3 Abrasives for each test example were produced in the same manner as in Sample 1, except that the thickness of the abrasive layer was 5 μm (Test Example 2) or 8 μm (Test Example 3).
[0043] Test Examples 4-6 Abrasives for each test example were produced in the same manner as in Test Example 1, except that the curing time was changed to 8 minutes (Test Example 4), 11 minutes (Test Example 5), or 14 minutes (Test Example 6).
[0044] Test Examples 7-9 The abrasives of this test example were manufactured in the same manner as in Test Example 1, except that the surface was treated with 5 parts by mass of a silane compound {epoxysilane (Test Example 7), vinylsilane (Test Example 8), phenylaminosilane (Test Example 9)} per 100 parts by mass of abrasive grains.
[0045] (Test 1) Using the abrasive of Test Example 1 and a commercially available abrasive (NTT-AT, ADS-127), 50 terminals of LC / PC connectors (zirconia ferrule, glass fiber) were fixed to a jig, and polishing was performed using a Bulls-3000 polishing machine. All pads used to fix the abrasives had a hardness of 80. Polishing was performed in five stages, with (a) diamond abrasive (9 μm), rotation speed of 130 rpm, 15 seconds, (b) diamond abrasive (30 μm), rotation speed of 130 rpm, 10 seconds, (c) diamond abrasive (9 μm), rotation speed of 130 rpm, 15 seconds, (d) diamond abrasive (1 μm), rotation speed of 130 rpm, 25 seconds, and (e) abrasive of each test example, rotation speed of 130 rpm, 25 seconds.
[0046] The LC / PC connectors, which were grouped into sets (a) to (e), were polished 1, 10, 20, 30, and 40 times, and the fiber end faces were observed under a microscope to determine whether there were scratches. The number of scratches was expressed as a percentage of the number of terminals on which scratches were observed out of a total of 50 terminals. The return loss of the fiber was measured using an optical connector characteristic measuring device (OLCR type reflectometer).
[0047] After polishing, the abrasive layer was observed to see whether it had peeled off from the support substrate, and the area of the peeled off area was measured. The ratio of the peeled off area to the total area of the abrasive layer was evaluated on a 6-point scale from 0 to 5. The following scores were assigned: 0 (no peeling at all), 1 (1-20% peeled off area), 2 (21-40% peeled off area), 3 (41-60% peeled off area), 4 (61-80% peeled off area), 5 (81-100% peeled off area (no coating film remaining)).
[0048] The end face shape of the LC / PC connector was measured in three dimensions to measure the height of the end face of the glass fiber with respect to the end face of the zirconia ferrule as the reference. The height of the end face was indicated by taking the direction in which the end face of the glass fiber is recessed with respect to the end face of the zirconia ferrule as the negative direction. The above results are shown in Table 1 (abrasive of Test Example 1) and Table 2 (commercially available product).
[0049] Here, scratches are preferably 50% or less. The return loss is preferably 57 dB or more. It is preferable that the polishing layer of the polishing material does not peel off. The fiber height is preferably within the range of ±20 nm.
[0050] [Table 1]
[0051] [Table 2]
[0052] As is clear from the table, with the abrasive of Test Example 1, the occurrence of scratches was below 50% up to 40 times, whereas with the commercially available product, the occurrence of scratches was already at 54% after 10 times, exceeding 50%, and showing generally high values except for the first time. The return loss rate was 60 dB for the abrasive of Test Example 1, and 53 dB for the commercially available product.
[0053] Peeling of the abrasive layer occurred more frequently in the commercially available product than in the abrasive material of Test Example 1. For example, even after 20 or more uses, the abrasive layer of the abrasive material of Test Example 1 did not peel off to the extent that it would cause problems in use. It was found that the fiber height of all the abrasives in Test Example 1 was within the preferred range, whereas the commercially available products were slightly lower.
[0054] (Test 2) The abrasives of Test Examples 2 and 3 were used to polish an LC / PC connector in the same manner as in Test 1. As a result, there was no significant difference from the abrasive of Test Example 1 in terms of scratch generation, return loss, and fiber height, but there was a tendency for peeling of the abrasive layer, which is related to durability, to increase as the thickness of the abrasive layer increases (Table 3).
[0055] [Table 3]
[0056] (Test 3) The abrasives of Test Examples 4 to 6 were used to polish LC / PC connectors in the same manner as in Test 1. As a result, there was no significant difference from the abrasive of Test Example 1 in terms of scratch generation, return loss, and fiber height, but there was a tendency for the abrasive layer to peel less as the curing time of the binder constituting the abrasive layer increased (Table 4). In addition, when the pencil hardness of Test Examples 1 and 4 to 6 was measured, it was 2H in Test Example 1, 2H in Test Example 4, 2H in Test Example 5, and 3H in Test Example 6.
[0057] [Table 4]
[0058] (Test 4) The abrasives of Test Examples 1 and 7 to 9 were subjected to the same test as Test 1. After that, the abrasives of each Test Example were observed for peeling, and it was found that the abrasives of Test Examples 7 to 9 peeled less and were more durable than the abrasive of Test Example 1.
Claims
1. A binder made of a resin material; abrasive grains dispersed in the binder; having The resin materials are all crosslinked, The abrasive grains are The content of the abrasive grains and the binder is 80% or more and 91% or less based on the sum of the masses of the abrasive grains and the binder, The abrasive grains are composed of 62.5% to 80% small particles having a particle diameter of 100 nm or less based on the mass of the abrasive grains, It is composed of silica, The resin material contains 93% or more of an epoxy resin based on the mass of the resin material, The epoxy resin is of the biphenyl type. Abrasive for ferrules.
2. 2. The abrasive for ferrules according to claim 1, wherein the binder has a pencil hardness of 3H or more.
3. 3. The abrasive for ferrules according to claim 1, wherein the small diameter particles have a peak top particle size of 50 nm or less.
4. 4. The abrasive for ferrules according to claim 1, wherein the abrasive grains contain grains having a peak top grain size of 150 nm or more.
Citation Information
Patent Citations
Polishing film and manufacturing method thereof
JP2007190613A
Abrasive grain for abradant, method for producing the same and abradant
JP2008001803A
Polishing sheet equipped with nano-silica polishing particles, and polishing method and manufacturing method for optical fiber connector using polishing sheet
WO2017098579A1
Multi-core ferrule polishing material
WO2020100848A1